N3X: Notation3 with SPARQL Expressions - Farnbauer-Schmidt, Matthias; Charpenay, Victor; Harth, Andreas (The Semantic Web: ESWC 2020 Satellite Events, 2020)
Writing calculations with many intermediate steps in Notation3 (N3) rules is complex and verbose. This issue is addressed by extending N3 with SPARQL expressions. In this paper, we introduce and evaluate the syntax of this approach, called N3X. In our examples N3X reduces the number of triples in calculation heavy N3 rules by 30%, the number of triples with a math:*-predicate by 65% and the number of non-blank characters by 24.4% on average.<br
Keywords: Notation3; N3X; SPARQL expressions